Simulation of ground operations at Changi Airport - Arunprasad Sarveshwar (2017)
Autonomous vehicles have been on the upswing ever since its introduction due to its reliability and the efficiency at which they operate. ST engineering has taken this initiative to develop Autonomous vehicles inside the Changi airport for providing better services to the passengers and to increase the efficiency of goods transportation. Before implementing the idea practically, it is important to check if the following can be implemented theoretically. Hence, the need for a simulation tool is imperative. Vissim, a simulator tool specifically to test the autonomous vehicles is used. Vissim facilitates us in creating links(roads), vehicles and obstacles which help in better visualization of the project. Several actions such as passengers arriving and departing at a gate and goods transportation from the Central Distributed factory to the respective gates and the vice versa is effectively put into action. COM port is not used here as control operations are done with the Vissim software itself. After several hardships, the final simulator is able to realistically represent the operations taking place inside the Changi Airport.